Validating field methods to estimate the pelvic tilt in sprinting and the relationship between prior hamstring injury and the pelvic tilt in elite female soccer players - Hegyi, A.; Sarcher, A.; Varenne, F.; Mornet, A.; Cadu, J.-P.; Carcreff, L.; Lacourpaille, L. (Journal of Human Kinetics, 2025)
An excessive pelvic tilt in the late swing phase of sprinting may be associated with an increased risk of hamstring injury. Nevertheless, research including female athletes is scarce. Furthermore, it is essential to validate simple on-field methods. This study consisted of two experiments. Experiment I assessed the validity of two 2-D video-based methods: i) the kick-back score calculated from thigh angles at the toe-off and the touchdown; and ii) the pelvic tilt estimated by a line connecting two markers on the pelvis. Twelve soccer players sprinted for 30 m, and 3-D motion capture data and 2-D sagittal plane video were recorded. Experiment II aimed to compare the above 2-D methods in recently injured (n = 7) and non-injured (n = 18) professional female soccer players. In Experiment I, no correlation was found between the kick-back score and the pelvic tilt assessed using 3-D motion capture (rho = -0.224, p = 0.242). Two-D camera-based estimation of the pelvic tilt correlated with the 3-D pelvic tilt (r = 0.89-0.94, p < 0.001). In Experiment II, the kick-back score was not significantly different between groups (d = 0.11, p = 0.41). The pelvic tilt was higher in the previously injured than in non-injured players in the late swing phase (d = -0.79, p = 0.03). Our results suggest that the kick-back score is not associated with the pelvic tilt. Nevertheless, the estimation of the pelvic tilt in field settings is feasible through the tracking of two markers on the pelvis in the sagittal plane. Additionally, longitudinal studies are recommended to gain deeper understanding of the excessive pelvic tilt in previously injured female soccer players.